2020
DOI: 10.1136/bmjopen-2020-037648
|View full text |Cite
|
Sign up to set email alerts
|

Eye health and quality of life: an umbrella review protocol

Abstract: IntroductionVision impairment and eye disease are major global health concerns and have been associated with increased morbidity and mortality, and lower quality of life. Quality of life, whether generic, vision-specific or disease-specific, is an important measure of the impact of eye health on people’s daily activities, well-being and visual function, and is increasingly used to evaluate the impact of ophthalmic interventions and new devices. While many studies and reviews have examined the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…VI is a major cause of disability worldwide, 21 and has been associated with increased mortality, 22 multiple chronic comorbidities, 23 , 24 anxiety and depression, 10 and decreased quality of life. 25 , 26 People with disabilities have been reported to be at higher risk of COVID-19 infection and worse outcomes, 27 but disease prevalence and outcomes amongst the visually-impaired have not been adequately examined. Our study was not intended to detect a difference between groups in regards to rate of infection, as only 1 participant overall reported being positive for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…VI is a major cause of disability worldwide, 21 and has been associated with increased mortality, 22 multiple chronic comorbidities, 23 , 24 anxiety and depression, 10 and decreased quality of life. 25 , 26 People with disabilities have been reported to be at higher risk of COVID-19 infection and worse outcomes, 27 but disease prevalence and outcomes amongst the visually-impaired have not been adequately examined. Our study was not intended to detect a difference between groups in regards to rate of infection, as only 1 participant overall reported being positive for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…315 The use of effective cataract surgical coverage (proportion of people aged 50 years or older with operated cataract or operable cataract who have a good postoperative presenting visual acuity) has only begun since 2017, with a total of 28 available reports representing few global regions (appendix 1 p 81). To supplement these reports and assess progress in the past two decades, we have reanalysed the data from 149 RAAB surveys from 48 countries (appendix 1 pp [84][85]. We then selected the most appropriate estimate available for each country.…”
Section: Progress Towards Universal Eye Health Coveragementioning
confidence: 99%
“…To summarise the extensive research on the impact of vision impairment, eye conditions, and ophthalmic interventions on the quality of life, we conducted an umbrella review of systematic reviews ( appendix 1 p 17 ). 85 In total, 69 systematic reviews were identified. Nine of those reviews evaluated the relationship between quality of life and vision impairment or specific eye conditions, such as age-related macular degeneration, glaucoma, or diabetic retinopathy, and all concluded that vision loss and eye disease were associated with poor quality of life outcomes.…”
Section: Section 2: the Importance Of Eye Healthmentioning
confidence: 99%
“…Limitations in daily functioning, independence, indoor and outdoor movement, social inclusion, communication and employment extend beyond the affected individual, and can have repercussions for the family and the community. 2 In addition, the current COVID-19 pandemic and its preventive measures pose a new set of challenges for people with visual impairment in performing daily living tasks by restricting their usual routine support and supplies. 3 People with visual impairment need to live independently and cope with daily challenges faced at home, workplace, school, and market.…”
Section: Introductionmentioning
confidence: 99%